2020
DOI: 10.1186/s43055-020-00223-0
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary ct manifestations of COVID-19: changes within 2 weeks duration from presentation

Abstract: Background: Coronavirus disease 2019 (COVID-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Chest computed tomography (CT) plays an essential role in the evaluation of COVID-19. This retrospective study aims to determine and compare the pulmonary changes in Iraqi patients with COVID-19 disease across the first two weeks after onset of symptoms using computerized tomography (CT) scan. Ninety-six patients with COVID-19 disease were enrolled in this study. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 17 publications
6
12
0
Order By: Relevance
“…The CT features of COVID-19 pneumonia in our study are compatible with that published in the literature [ 20 23 ]. Ground glass opacities were the most common CT chest radiological finding with bilateral peripheral/subpleural predilection.…”
Section: Discussionsupporting
confidence: 90%
“…The CT features of COVID-19 pneumonia in our study are compatible with that published in the literature [ 20 23 ]. Ground glass opacities were the most common CT chest radiological finding with bilateral peripheral/subpleural predilection.…”
Section: Discussionsupporting
confidence: 90%
“…The WHO and NICE recommendations support that only symptoms are enough to suspect infected cases, 5,10 so the majority of the pharmacists relied on patient symptoms to identify COVID‐19 presumptive cases, but the process of case identification and differentiating symptoms from common cold and flu or other respiratory diseases without the confirmation with the PCR swap may be very complex 14,18 . Moreover, patients with COVID‐19 may experience leucopenia, thrombocytopenia, and lymphopenia; however, high levels of serum C‐reactive protein (CRP), Erythrocyte sedimentation rate (ESR), lactate dehydrogenase (LDH), D‐dimer, and kidney function tests may be seen 18‐20 . Consequently, pharmacists ordered certain laboratory tests and chest CT scans to assess patient condition and define disease progression, which indicates that pharmacists can offer suitable guidance for patients and communicate proper clinical knowledge when possible.…”
Section: Discussionmentioning
confidence: 99%
“…Multislice CT chest has a sensitivity of 97% and 75% in PCR positive and negative cases respectively with 25% specificity for detection of COVID-19 infection, many studies have reported CT pulmonary changes with COVID-19 [ 27 , 33 ] which were combined in a prognostic score predicting the mortality in COVID-19 infected patients [ 34 ]. The most common observed CT changes were multiple bilateral peripheral GGO [ 35 ]. Many reports demonstrated a positive correlation between CT changes and abnormal blood coagulation parameters (based on measurements of platelets and D-dimer) [ 23 , 36 , 37 ], our results agreed with the previous studies where only patients with moderate GGO had a significantly higher D-dimer level compared with free CT, furthermore, our results in alignment with Zhang et al [ 23 ], demonstrated an association between CRP, and serum ferritin with the severity of CT changes.…”
Section: Discussionmentioning
confidence: 99%